Pengaruh Perilaku Kewirausahaan dan Pemasaran Terhadap Pendapatan Pada Toko Sembako di Desa Tempuran Trimurjo - Yunita, Nurma; Iskandar AA (Jurnal EMT KITA, 2023)
Entrepreneurship is one of the main driving forces that determine the development and decline of the economy, because in the field of entrepreneurship there is freedom of creativity. The large number of people operating grocery stores means prices are becoming tighter, which could affect Tempuran Village grocery store's earnings. Payment at the Tempuran Village grocery store still uses a manual system, without computers, so customers often line up at the checkout counter to pay. The purpose of this study is to determine the influence of business and marketing behavior on the income of a basic food store in the village of Tempuran Trimurjo. This type of research is quantitative. The population in this study were grocery store business owners in Tempuran Trimurjo Village, with a total of 30 people. Data analysis uses multiple linear regression tests. The results of this research conclude that there is a positive and significant influence between entrepreneurial behavior on income at the basic food shop in Tempuran Trimurjo Village. Apart from that, there is also a positive and significant influence between marketing on income at the basic food shop in Tempuran Trimurjo Village. There is a positive and significant influence between entrepreneurial behavior and marketing on income at the basic food shop in Tempuran Trimurjo Village.